2019
DOI: 10.1108/nfs-06-2018-0169
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hypertensive, anti-diabetic, hypocholesterolemic and antioxidant properties of prickly pear nopalitos in type 2 diabetic rats fed a high-fat diet

Abstract: Purpose The purpose of this study was to investigate the effects of prickly pear (Opuntia ficus indica (OFI)) nopalitos on body weight, food consumption, arterial blood pressure, glucidic homeostasis, cholesterol metabolic pathway and tissues redox status in type 2 diabetic (T2D) rats fed a high-fat diet (HFD). Design/methodology/approach Rats were fed by a HFD containing 30 per cent sheep fat for 10 weeks, after which they were rendered diabetic by an injection of a low dose of streptozotocin (STZ) (35 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…The chemistry of sterols and triterpenoids of some species, from the subfamily Cactoideae, tribe Phyllocacteae, mainly from the subtribe Echinocereinae, was reviewed, together with their biological activities. The information generated about the sterols reveals the presence of the typical 5 sterols like sitosterol, among others, but interestingly the presence of a very unusual family of 8 sterols with a pattern of oxidation in a sterol moiety of 27 carbons. Two sterols are of biosynthetic importance because it appears as unusual intermediaries in a truncated demethylation process.…”
Section: Discussionmentioning
confidence: 99%
“…The chemistry of sterols and triterpenoids of some species, from the subfamily Cactoideae, tribe Phyllocacteae, mainly from the subtribe Echinocereinae, was reviewed, together with their biological activities. The information generated about the sterols reveals the presence of the typical 5 sterols like sitosterol, among others, but interestingly the presence of a very unusual family of 8 sterols with a pattern of oxidation in a sterol moiety of 27 carbons. Two sterols are of biosynthetic importance because it appears as unusual intermediaries in a truncated demethylation process.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study has shown that OFI cladodes supplementation in a high-fat diet improved effectively blood pressure in rats with diabete type 2 (DT2) (Harrat et al , 2019). Similarly, others authors (Bakour et al , 2017) showed that the intravenous administration of the freeze-dried extract of OFI stems generates a significant decrease in blood pressure in rabbits as well as a rise in urinary volume and urinary excretion of sodium, which could explain its hypotensive effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the chemical composition of the edible cladodes from Opuntia ficus indica (OFI) show that this food has a high nutritional value, mainly due to their proteins, fibers and phytochemical contents (Rodriguez-Garcia et al , 2007; Hernández-Pérez et al , 2005; Ayadi et al , 2009; Rodríguez-Félix and Cantwell, 1998). Interestingly, antioxidant activity has also been reported (Kuti, 2004; Corral-Aguayo et al , 2008; Harrat et al , 2019; Chekkal et al , 2020). The use of animal models with diet-induced obesity helps to evaluate the nutritional values and some biological parameters of OFI nopalitos (Morán-Ramos et al , 2012; Kang et al , 2013); among these models, the cafeteria diet (CD) makes use of grocery store-purchased food items that more closely approximate the human ultra-processed diet (processed foods are basically made by adding salt, oil, sugar or additives such as artificial colors flavors and stabilizers) (Monteiro et al , 2019) than commercial high-fat or high-sugar rodent's diets (Gomez-Smith et al , 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Among animal studies, five showed significant reductions in BP. [34][35][36][37][38] In the first study, 34 24 male Sprague-Dawley rats were randomly divided into four groups: I (control), II (diabetic), III (low dose), and IV (high dose). Group II, III and IV were given Streptozotocin (STZ) injection to induce diabetes.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Harrat et al reported similar finding in their study. 37 Briefly, male Wistar rats (n = 12) were divided into two groups and were put on a high-fat diet for 10 weeks before being rendered diabetic via STZ. One group was supplemented with 5% (of total diet weight) of freeze-dried cactus pear powder on top of their ongoing high-fat diet while the other group received no treatment for a duration of 30 days.…”
Section: × 800 Iu Capsulementioning
confidence: 99%